Personal values and willingness to pay for fair trade coffee in Cape Town, South Africa. (1st December 2019) - Lappeman, James; Orpwood, Tessa; Russell, Meghan; Zeller, Tatiana; Jansson, Johan
Abstract: Understanding ethical buying behaviour is an important component in the study of sustainability. Multiple studies on fair trade have been conducted in established markets in Europe, with limited but increasing research in emerging markets. This study used a questionnaire survey to investigate South African consumers' ethical buying behaviour, using conjoint analysis to imitate the multi-attribute decision consumers face when buying coffee. Based on previous research, factors concerning consumers' personal values, willingness to pay, and knowledge are combined. In the results, participants were segmented based on their willingness to pay for fair trade labelled coffee and these segments were then compared in terms of their fair trade knowledge and personal values. The study profiled four different segments and concluded that conventionalism, rationalism, sincerity, and personal satisfaction did not differ significantly across segments. The segment 'Fair Trade Lovers', however, exhibited higher levels of humanitarianism than the segment 'Brand Likers', and were willing to pay a higher fair trade premium. While knowledge of fair trade did not differ significantly between segments, the total sample displayed above average fair trade knowledge and 63% were willing to pay a 10% premium. Insights from this study suggest that marketing managers promoting fair trade in emerging markets can design more effective targeting and promotional strategies by highlighting the psychological determinants affecting the willingness to pay for fair trade products. Highlights: South African consumers' fair trade coffee purchasing behaviours are analysed. Four different segments of consumers are profiled based on their knowledge and values. The segment "Fair Trade Lovers" consisted of significantly more Brand Likers. Of the sample, 63% were willing to pay a 10% price premium for fair trade coffee.